2012
DOI: 10.1086/662657
|View full text |Cite
|
Sign up to set email alerts
|

Galápagos and Cocos Islands: Geographically Close, Botanically Distant

Abstract: We investigated whether the plants of the Galápagos Archipelago and Cocos Island, which are each other's closest neighboring insular systems, show any such sister relationships. Five genera of vascular plants have endemics in both archipelagos, including plants with different life histories and dispersal mechanisms: tree ferns, epiphytes, trees, herbs, and shrubs, with adaptations for dispersal by wind or birds (two genera each) or with no obvious dispersal adaptation (one genus). We obtained molecular phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 75 publications
3
12
0
1
Order By: Relevance
“…The few phylogenies published for Galápagos plants suggest that continental ancestors may have colonized from many different areas including the Caribbean, Ecuador, Peru and Chile (Tye & Francisco‐Ortega, ; Trusty et al ., ). Phylogeographic and phylogenetic analyses revealed a single, independent dispersal event by Galvezia from the mainland to the Galápagos archipelago (Figs and ).…”
Section: Discussionsupporting
confidence: 93%
“…The few phylogenies published for Galápagos plants suggest that continental ancestors may have colonized from many different areas including the Caribbean, Ecuador, Peru and Chile (Tye & Francisco‐Ortega, ; Trusty et al ., ). Phylogeographic and phylogenetic analyses revealed a single, independent dispersal event by Galvezia from the mainland to the Galápagos archipelago (Figs and ).…”
Section: Discussionsupporting
confidence: 93%
“…Comparisons of putative relatives based on taxonomy have recently become possible by phylogenetic reconstructions, and the sister-group principle has been used to infer some characteristics of the most recent common ancestor of endemic species (Vargas, 2007). Unfortunately, there are only a few phylogenetic analyses of Galápagos plant groups available to address this issue, and those with a reliable sample do not show any tendency to loss of dispersability (Sánchez-del Pino, Motley & Borsch, 2012;Vargas et al, 2012; see also Trusty et al, 2012). A lineage-by-lineage reconstruction of sister-group relationships is needed on a considerable number of plant groups to test diaspore shifts.…”
Section: Loss Of Dispersabilitymentioning
confidence: 99%
“…Recent phylogenetic studies have demonstrated that the closest relatives of some island endemics are not always from the mainland but rather from neighboring islands (Sato et al 1999;Motley et al 2005;Harbaugh and Baldwin 2007;Andrus et al 2009;Namoff et al 2010), emphasizing the contributions of both continents and islands to insular biodiversity. Trusty et al (2012) recently investigated whether the plants of the Galápagos Archipelago and Cocos Island, which are each other's closest neighboring insular systems, show any such sister relationships. Using molecular phylogenetic data for all five genera of vascular plants with endemics in both island locations, Trusty et al (2012) demonstrated no evidence for any phylogeographical links between the islands.…”
Section: Introductionmentioning
confidence: 99%
“…Trusty et al (2012) recently investigated whether the plants of the Galápagos Archipelago and Cocos Island, which are each other's closest neighboring insular systems, show any such sister relationships. Using molecular phylogenetic data for all five genera of vascular plants with endemics in both island locations, Trusty et al (2012) demonstrated no evidence for any phylogeographical links between the islands. This lack of floristic affinity between Galápagos and Cocos was attributed primarily to atmospheric and ocean circulation patterns that likely limit dispersal between the two.…”
Section: Introductionmentioning
confidence: 99%